Negative effects of a piscicide, rotenone, on the growth and metabolism of three submerged macophytes. (July 2020) - Wu, Ai-Ping; He, Yu; Ye, Shi-Yun; Qi, Liang-Yu; Liu, Li; Zhong, Wen; Wang, Yan-Hong; Fu, Hui
Abstract: A piscicide, rotenone (RT), is frequently used for clear and management of aquatic systems such as fish pond, and even for illegal fishing throughout the world. The effects of RT on submerged macrophytes remain elusive although the effects of RT on many kinds of animals are well documented. We wanted to determine the effects of RT on the growth and metabolism of three submerged plants ( Vallisneria natans, Myriophyllum spicatum, Potamogeton maackianus ) and try to find the reasons of these effects. The results showed that the shoot height, shoot dry weight, root dry weight, root:shoot ratios, contents of soluble protein and soluble carbohydrate of the three tested submerged plants were significantly negatively affected by RT and the effects were different among the studied species. Furthermore, pH rised a little and light transmission was greatly reduced in the water with RT treatment. We think that the negative effects of RT on the growth and metabolism of submerged species is partially attributing to the lower light caused by RT application. Accordingly, we highlight that submerged species may be greatly suppressed by RT, and we should apply RT in water ecosystems with great caution. Graphical abstract: Image 1 Highlights: No reports of rotenone effects on submerged plants. Negative effects of rotenone on studied submerged plants. Indirect toxicity of low light transmission causes negative effects. Rotenone application in water should be with great caution.